The Influence Of Independence, Auditor Experience, Professionalism, Auditor Motivation, And Competence On Auditor Performance In Accounting Firm In Bali - Ni Nyoman Ayu Suryandari; Kadek Kartika Wulandewi (Jurnal Mantik, 2022)
A financial report is said to be reliable if the financial report has been examined by an independent third party. The party that examines the financial statements of a company is called an independent auditor. This research was conducted with the aim of knowing the effects of independence, auditor experience, professionalism, auditor motivation, and competence on auditor performance at KAP in Bali Province. The population in this study were 108 auditors at 18 KAPs in Bali. The sample in this study were 67 respondents, however, the final sample that filled out the questionnaire was 61 respondents. The analysis technique used in this study is multiple linear regression analysis. The results of this study indicate that independence, professionalism, and competence have a positive effect on the performance of auditors at KAPs in the Province of Bali. Meanwhile, auditor experience and auditor motivation have no effect on auditor performance at KAP in Bali Province.